Chronic Cognitive Impairment in AQP4+ NMOSD With Improvement in Cognition on Eculizumab: A Report of Two Cases - Saab, Georges; Munoz, David G.; Rotstein, Dalia L. (Frontiers in Neurology, 2022)
Cognitive impairment may be associated with aquaporin-4 antibody positive (AQP4+) NMOSD, particularly where there is prominent cerebral, corpus callosum, or thalamic involvement. It is unclear to what extent this phenomenon may be treatable after months to years. We describe two cases of AQP4+ NMOSD with cognitive impairment persisting over more than 6 months, where cognition improved after eculizumab was initiated. In the first case, a 51-year-old woman presented with a two-month history of cognitive decline and ataxia, and diffuse involvement of the corpus callosum on MRI. AQP4 antibody testing returned positive. Cognitive impairment persisted on therapy with mycophenolate, then rituximab. She was switched to eculizumab from rituximab 18 months after disease onset because of breakthrough optic neuritis; memory and cognitive function improved on eculizumab. In the second case, a 26-year-old woman initially presented with visual, auditory and tactile hallucinations, and impairment in activities of daily living, and was given a diagnosis of schizophrenia. Nine months later she was hospitalized for increasing confusion. MRI showed leukoencephalopathy and diffuse involvement of the corpus callosum with multiple enhancing callosal lesions. AQP4 antibody testing was positive and CSF testing for other antibodies of autoimmune encephalitis was negative. She had some improvement in cognition with high dose corticosteroids but remained significantly impaired. On follow-up, her repeat MRI showed a small new right inferomedial frontal enhancing lesion although she did not complain of any new cognitive issues, her MOCA score was 21/30, and she was started on eculizumab. Two months after eculizumab initiation she and her family reported cognitive improvement and MOCA score was 25/30. Common features of these two cases included extensive callosal involvement and an element of ongoing gadolinium enhancement on MRI. Our experience suggests the possibility that cognitive impairment may be amenable to immunotherapy in certain cases of NMOSD.